The method of the military-economical estimate and choice of peacemaking operation’s versions from the whole complex of alternatives - Huliak, О. V. (Honor and Law, 2019)
The article deals with the criterion of “effectiveness – value – time ” for the military-economical estimate and choice of the best alternative from the whole complex of possible peacemaking operations, which maximizes the index in a state of the norm increase of the effectiveness of the peacemaking`s system under it`s use, which is related to the average geometrical increase of finances and time`s expenses for the implementation of such an operation.